(untitled) (Research, Society and Development, 2024)
Objective: the scoping review protocol aims to map the literature regarding scientific knowledge about obstetric violence and good practices in labor and birth, in the national and international context at primary and hospital levels. Methodology: the development of the protocol was guided by the guidelines of the Joanna Briggs Institute and the PRISMA Extension for Scoping Reviews (PRISMA-ScR). Five methodological steps will be carried out to prepare the scoping review, which will identify the types of evidence available on good practices in labor and birth and obstetric violence, clarify its main concepts/definitions in the literature, identify the main characteristics and related factors to themes. The search will take place in the databases: MEDLINE, Virtual Health Library (VHL), CAPES and LILACS Periodicals. Articles and guidelines published by national and international health bodies will be included. Included articles will be imported into Endnote and Rayyan software. In the first, the management of references and removal of duplicates will be processed and in the second, the selection of studies will be carried out. Final considerations: it is noteworthy that the data collected will support the construction of an educational booklet that will focus on guiding pregnant women about obstetric violence, labor and birth. The protocol was registered on Figshare to ensure transparency and visibility of the review process.